Characteristics of Pediatric Crohn’s Disease in Saudi Children: A Multicenter National Study - Omar I. Saadah; Mohammad El Mouzan; Mohammad Al Mofarreh; Ali Al Mehaidib; Mohammad Al Edreesi; Mohammed Hasosah; Abdulrahman Al-Hussaini; Khalid AlSaleem (Gastroenterology Research and Practice)
Background and Aims. Crohn’s disease (CD) is an evolving disease in KSA. Little is known about its characteristics in the Saudi population. The aims of this study were to describe the characteristics of Saudi children with CD and to determine whether the characteristics of CD in KSA are different from those seen in Western countries. Methods. In this study, children younger than eighteen years of age diagnosed with CD between January 2003 and December 2012 were included. Results. Of 330 patients identified, 186 (56.4%) were males. The median age at diagnosis was 15.8 years. A positive family history for IBD in first-degree relatives occurred in 13.6% of patients. The most common symptoms were abdominal pain (84.2%), weight loss (75.2%), and diarrhea (71.8%). The main disease location was ileocolonic (42.1%) and the main disease behavior was nonstricturing and nonpenetrating (63.6%). Perianal involvement was seen in 60 (18.2%) patients. Laboratory findings revealed anemia in 57.9% of patients, low albumin in 34.5%, and high CRP in 39.4%. Conclusions. Saudi children with CD have lower frequency of first-degree relatives with IBD, lower prevalence of early onset disease, longer diagnostic delay, higher prevalence of growth failure, and greater frequency of stricturing and penetrating disease behavior compared to Western patients.